1996
DOI: 10.1080/01635589609514472
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic effect of a mammalian lignan precursor from flaxseed

Abstract: Secoisolariciresinol diglycoside (SD), a mammalian lignan precursor found in high-fiber foods, was isolated from flaxseed and tested for effects on mammary tumorigenesis in rats fed a high-fat (20%) diet. Ingestion of purified SD at 1.5 mg/day for 20 weeks starting 1 week after treatment with the carcinogen dimethylbenzanthracene resulted in a 37% reduction (p < 0.05) in the number of tumors per tumor-bearing rat and a 46% reduction (p < 0.05) in the number of tumors per tumor-bearing rat and a 46% reduction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
2
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(140 citation statements)
references
References 28 publications
3
129
2
6
Order By: Relevance
“…As it is well documented that plant lignans also have potent antitumorigenic activity with minimal side effects (Thompson et al, 1996;Bylund et al, 2005;Saarinen et al, 2008), we tested whether this activity could involve sensitization to death receptor signaling. A number of closely related lignans ( Figure 1a) were tested in a non-toxic concentration for their capacity to sensitize LNCaP prostate cancer cells to TRAIL receptor-mediated apoptosis in the prescence or absence of androgen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is well documented that plant lignans also have potent antitumorigenic activity with minimal side effects (Thompson et al, 1996;Bylund et al, 2005;Saarinen et al, 2008), we tested whether this activity could involve sensitization to death receptor signaling. A number of closely related lignans ( Figure 1a) were tested in a non-toxic concentration for their capacity to sensitize LNCaP prostate cancer cells to TRAIL receptor-mediated apoptosis in the prescence or absence of androgen.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that lignans inhibit proliferation and are cytotoxic to prostate cancer cell lines (Lin et al, 2001, Chen et al, 2007. Moreover, lignans can prevent tumor growth and induce apoptosis in vivo in prostate cancer xenografts or chemically induced mammary tumors (Bylund et al, 2005;Saarinen et al, 2008;Thompson et al, 1996) and can also reduce experimental metastasis (Li et al, 1999). Plant-derived lignans, such as matairesinol (MAT), are metabolized by mammalian gut microflora resulting in enterolactone (ENL) or enterodiol (Axelson et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In another study the flax lignan SDG was fed to mice starting 1 week after treatment with the carcinogen dimethylbenzanthracene. The number of tumors per rat was reduced by 46% compared to the control in this study [71]. Flax or its lignan (SDG) were tested to see if they would prevent melanoma metastasis.…”
Section: Reviewmentioning
confidence: 99%
“…After estrogen deprivation, SP and its isoflavone genistein have been shown to increase the growth of the MCF-7 tumors in ovariectomized animals, [9][10][11] while no stimulation of MCF-7 tumor growth has been observed when mice were exposed to FS 12 or its mammalian lignan metabolites, enterodiol and enterolactone. 11 In addition, FS, SDG and enterolactone have been shown to reduce the growth of the dimethylbenzanthracene (DMBA)-induced hormone responsive mammary tumors in nonovariectomized rats, [13][14][15] suggesting a protective role of lignan-rich diets and enterolactone in breast cancer.…”
mentioning
confidence: 99%